Psychological features of the educational motivation of persons with the status of orphans and children deprived of parental care (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the problem of the formation ofpositive motivation in people with the status of an orphan (child deprivedof parental care). The specificity of the terms of becoming the personalityof orphans is emphasized as a circumstance for varying the motivationalsphere of the subjects. The results of an empirical study of the orientationof the educational motivation of people with the corresponding statusare presented, based on the dominance of one of the motives — achievingsuccess or avoiding (fear) failure in educational and professional activities.The results obtained are compared with the indicators of subjects whowere brought up in parental families. The conclusion is drawn about thegeneral trend of the dominance of positive educational motivation amongsubjects, including orphans.
Keywords: positive motivation; leading motives; orphanhood; the formation of the personality of an orphan; educational motivation